Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Pt. Fajar Riau Wisata Pekanbaru - Dehotman, Khornelis (Eko dan Bisnis: Riau Economic and Business Review, 2022)
This research was conducted at PT. Fajar Riau Wisata Pekanbaru Jl. Soekarno-Hatta no. 61 Tangkerang Barat Kec. Marpoyan Damai Pekanbaru. The purpose of this study was to determine the effect of service quality on customer satisfaction at PT. Fajar Riau Wisata Pekanbaru. In analyzing the data obtained from the object of research using quantitative analysis and the number of respondents is 100 people, using the SPSS 24 program using the simple linear regression analysis method. Based on the discussion with simple linear regression, the resulting regression equation is Y = 32.740 + 0.426 X, meaning that the value of a is 32.740, this value indicates that when the Service Quality variable (Variable X) is zero, then Customer Satisfaction (Variable Y) is worth 32,740. While the value of b is 0.426. This means that every increase in perception of service quality by 1 unit, it will increase perceptions of customer satisfaction by 0.426. The result is that t count (3.298) > t table (1.98447) and significance (0.001) < 0.05. Thus, Ho is rejected and Ha is accepted. This means that there is a significant effect of service quality variables on customer satisfaction at PT. Fajar Riau Wisata Pekanbaru. The direction of the influence is positive. This means that the better the quality of service it will increase customer satisfaction at PT. Fajar Riau Wisata Pekanbaru. The value of the coefficient of determination (R2 ) is 0.100. This means that the contribution of the influence of service quality on customer satisfaction at PT. Fajar Riau Wisata Pekanbaru is 10%, while the remaining 90% is influenced by other variables not included in this study.